Mexico : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report offers several policy recommendations aimed at improving the accounting and auditing regulatory framework. An important aspect is the strengthening of enforcement mechanisms for ensuring compliance with accounting and auditing requirements and auditors' professional code of ethics; in this context, a recommendation has been made for the establishment of an independent oversight body for the audit profession. The review of accounting and auditing standards and practices in Mexico, which forms the basis of this report, placed specific focus on the strengths and weaknesses of the institutional framework that supports the corporate financial reporting system in the country. In that context, specific emphasis was placed on the quality and consistency of academic curricula for public accountants, as well as on existing arrangements for the licensing of auditors.